Evaluation of the Impact of Educational Games on The Literacy Capabilities of Elementary School Students - Zara Ali (Al-Hijr: Journal of Adulearn World, 2026)
The integration of educational games into the learning process has garnered significant attention due to their potential to enhance student engagement and learning outcomes. Particularly in elementary education, where foundational skills such as literacy are developed, educational games are seen as a promising tool for improving literacy capabilities. However, the impact of educational games on literacy skills in elementary school students remains underexplored. This study aims to evaluate the impact of educational games on the literacy capabilities of elementary school students. The primary objective is to assess how different types of educational games influence the development of reading, writing, and comprehension skills among young learners. A quasi-experimental research design was employed, involving 120 elementary school students across four classes. The students were divided into an experimental group, which engaged in educational game-based learning, and a control group, which followed traditional literacy instruction. Data was collected through pre- and post-tests measuring literacy skills, as well as surveys to gather student feedback. The results showed that the experimental group demonstrated significant improvements in reading comprehension, vocabulary, and writing skills compared to the control group. Students in the experimental group reported increased engagement and motivation towards literacy activities. This study concludes that educational games can significantly enhance literacy capabilities in elementary school students, providing a more engaging and effective approach to teaching foundational literacy skills.